Perspectives on How Human Simultaneous Multi-Modal Imaging Adds Directionality to Spread Models of Alzheimer’s Disease - Neitzel, Julia; Nuttall, Rachel; Sorg, Christian (Frontiers in Neurology, 2018)
Previous animal research suggests that the spread of pathological agents in Alzheimer’s disease (AD) follows the direction of signalling pathways. Specifically, tau pathology has been suggested to propagate in an infection-like mode along axons, from transentorhinal cortices to medial temporal lobe cortices and consequently to other cortical regions, while amyloid-beta (Aβ) pathology seems to spread in an activity-dependent manner among and from isocortical regions into limbic and then subcortical regions. These directed connectivity-based spread models, however, have not been tested directly in AD patients due to the lack of an in-vivo method to identify directed connectivity in humans. Recently, a new method - metabolic connectivity mapping - has been developed and validated in healthy participants that uses simultaneous FDG-PET and resting-state fMRI data acquisition to identify directed intrinsic effective connectivity. To this end, postsynaptic energy consumption (FDG-PET) is used to identify regions with afferent input from other functionally connected brain regions (resting-state fMRI). Here, we discuss how this multi-modal imaging approach allows quantitative, whole-brain mapping of signalling direction in AD patients, thereby pointing out some of the advantages it offers compared to other effective connectivity methods (i.e. Granger causality, dynamic causal modelling, Bayesian networks). Most importantly, metabolic connectivity mapping provides the basis on which models of pathology spread, derived from animal studies, can be tested in AD patients. In particular, future work should investigate whether tau and Aß in humans propagate along the trajectories of directed connectivity in order to advance our understanding of the neuropathological mechanisms causing disease progression.